Sugarcane bagasse: Properties, production and uses - Antunes, F. A.F.; Chandel, A. K.; Ingle, A. P.; Milessi, T. S.S.; Dussan, K. J.M. [UNESP]; Silva, D. D.V.; Teran-Hilares, R.; Brumano, L. P.; Silva, G. M.; Hernandez-Perez, A.; Ramos, L.; Carneiro, B. C.; et al. (My University, 2018)
Sugarcane bagasse is considered as a by-product from the sugaralcohol industries. However, from the last few decades, this biomass has been used mainly for energy generation by burning it in boilers. Moreover, after unraveling methods to obtain its carbohydrates portion such as cellulose and hemicellulose, this lignocellulosic material has been receiving a great deal of attention aimed to be used as a carbon source in various bioprocess and for other applications. Considering the widespread uses of sugarcane bagasse, this chapter focused on detailed information about the main producers of sugarcane and world availability for its plantation. Moreover, various techniques available for the characterization of the chemical and physical characteristics of sugarcane bagasse are also discussed. In addition, traditional uses and applications of sugarcane bagasse in energy, animals feed and others sectors have been also explained. Moreover, different approaches to extract the cellulosic and hemicellulosic fractions and its use as a carbon source for the production of different byproduct are also described.